Early detection model to prevent the damaging impact of political buzzer attacks on social media - M. Yusuf Samad; Armin Arsyad; Gustiana A Kambo (Department of Government Studies, Universitas Muhammadiyah Makassar, 2025)
Using buzzers in product marketing is common and part of a marketing communication strategy. However, the use of buzzers has shifted to the political realm, causing negative impacts such as manipulating public opinion by spreading false information and propaganda. A number of countries have utilized buzzers for propaganda and public opinion manipulation purposes, such as Russia, the Philippines, Malaysia and Indonesia. This study aims to formulate an early detection model to prevent the damaging impacts of using political buzzers attacks on social media by referring to the AISAS (Attention, Interest, Search, Action, and Share) model. This study uses a qualitative approach with data characteristics in the form of words, images, or sentences and includes many quotes and examples. The study results show that political buzzers on social media can be controlled strategically. The core of this strategy is to disrupt the buzzers' work process and strengthen the community's digital literacy because the digital literacy program that has been conducted has proven to be ineffective. Through the early detection model in this study, this can be done by disrupting the work process of buzzers and strengthening digital society through digital literacy by referring to the AISAS model. In addition, it is necessary to strengthen regulations by tightening account registration rules and clarifying law enforcement for the use of buzzers attacks.